2018
DOI: 10.1177/1403494818755600
|View full text |Cite
|
Sign up to set email alerts
|

People diagnosed with dementia in Sweden: What type of home care services and housing are they granted? A cross-sectional study

Abstract: Most people with a dementia diagnosis were living in ordinary housing, and, surprisingly, half of those did not receive any type of home care service. This knowledge is essential for making the living conditions and needs of people living with dementia more visible and to provide good home care services for people with dementia and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 20 publications
4
45
1
5
Order By: Relevance
“…In addition, onefifth of people with dementia utilize day centres. International studies have reported similar tendencies of low use of community healthcare services (Brandao, Ribeiro, & Martin, 2016;Nelson et al, 2002;Odzakovic, Hyde´n, Festin, & Kullberg, 2018). Simultaneously, the unmet care needs among persons with dementia and their family caregivers are substantial (Black et al, 2013;Forbes, Morgan, & Janzen, 2006;Kerpershoek et al, 2017;van der Roest et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, onefifth of people with dementia utilize day centres. International studies have reported similar tendencies of low use of community healthcare services (Brandao, Ribeiro, & Martin, 2016;Nelson et al, 2002;Odzakovic, Hyde´n, Festin, & Kullberg, 2018). Simultaneously, the unmet care needs among persons with dementia and their family caregivers are substantial (Black et al, 2013;Forbes, Morgan, & Janzen, 2006;Kerpershoek et al, 2017;van der Roest et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Notably, male care recipients used more respite care services than female care recipients, whereas male family caregivers reported the use of fewer services than female family caregivers. Female caregivers might have increased need for these services, as they are more likely to cohabit with the care recipient (Odzakovic et al, 2018) and to report higher levels of burden and depression, and lower levels of subjective well-being and physical health (Pinquart & Sorensen, 2006). The use of home-based and respite care service was more frequent among those who lived in urban areas compared to those who lived in rural areas.…”
Section: Factors Associated With the Use Of Servicesmentioning
confidence: 99%
“…Existing research has shown that people with dementia are at risk of becoming isolated in their homes (Aminzadeh, Dalziel, Molnar, & Garcia, 2010;World Health Organization, 2012). In Sweden, a great majority of people with dementia (about 72 percent) are living at home and around half of these are in single households (Odzakovic, Hydén, Festin, & Kullberg, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These numbers are expected to nearly double over the next 20 years (Wimo et al, 2014). A recent study showed that 72 per cent of all people diagnosed with dementia live in ordinary housing (Odzakovic, Hyd en, Festin, & Kullberg, 2019). This should be seen in addition to the fact that 75 per cent of all people 80 years or older in the Nordic countries live in single households (Nordic Welfare Centre, 2013a, 2013b.…”
Section: Introductionmentioning
confidence: 99%